Asesmen Pembelajaran Pada Masa Pandemi Covid-19 di Sekolah Menengah Pertama Jubilee Jakarta Utara - Ernawati Ernawati; Eri Theresina; Linda Pertiwi; Muji Rahayu (Equilibrium: Jurnal Pendidikan, 2022)
Activities in people's lives during the COVID-19 pandemic have undergone many changes. One of the activities in the teaching and learning process. Different strategies in conducting learning assessments during the pandemic are urgently needed. This is because the conditions of students and teachers are different in carrying out the learning and teaching process. This study aims to (1) find out the learning assessment process carried out by Jubilee Middle School teachers during the pandemic, (2) find out what obstacles teachers experience in conducting learning assessments during the pandemic. This research is an exploratory descriptive study, which describes and reveals the implementation of learning assessments during the pandemic. The population in this study were teachers of Jubilee Junior High School, North Jakarta. Determination of the sample with a saturated sample, where all teachers at Jubilee Junior High School, North Jakarta were sampled, as many as 15 teachers. Data were collected using questionnaires and interviews. interviews were conducted with teachers of English, Chemistry, Sports and Mathematics. Based on the results of data analysis, it was found that during the pandemic, teachers paid more attention to student activities during the learning process. Student participation in discussions, student attendance, and student attitudes in responding to questions from the teacher in the classroom are the teacher's considerations in conducting affective learning assessments. As for cognitive assessments, the limited supervision of students when carrying out tasks makes the results obtained feel less accurate for the teacher. In addition, the reduced duration of each subject and the lack of opportunities for students to practice using equipment that meets the criteria are also obstacles faced by teachers during the pandemic.